The AIDS crisis: Unethical marketing leads to negligent homicide - Krohn, Franklin B. (Journal of business ethics, 1989)
The purpose of this paper is to demonstrate how condom manufacturers and their marketers have failed to adequately promote their product to the male homosexual population (gays). Inasmuch as the AIDS syndrome constitutes a major life-threatening danger and that gays appear to be particularly vulnerable, failure to aggressively promote a known preventive such as condoms to gays constitutes negligent homicide., The method used here defines what is traditionally viewed as a viable “target market,” analyzes the major elements of marketing with regard to gays, and examines the neglect of condom promotion by their manufacturers., It is concluded that condom marketers have failed to promote a known protection against AIDS to a highly susceptible group. That group would normally be seen as a highly attractive market for condoms and were it not for homophobia, marketers would zealously pursue more aggressive promotion of condoms to gays.